MONITORING MODEL OF EDUCATIONAL ORGANIZATIONS' INNOVATION ACTIVITY - N. Kunitsyna (Вестник Северо-Кавказского федерального университета, 2022)
Rapid development of new technologies, innovative breakthrough in many sectors of the Russian economy have led to the introduce innovations in the educational environment as well. It is possible to assess the effectiveness of innovation activities of educational organizations on the basis of an integrated model of its monitoring, which are the basis of this article. The model integrates goal, tasks, conditions, principles, functions, resources, research stages, approaches, methods, criteria. The model is aimed at highlighting the goal and purpose of innovative changes, determining their compliance with the current conditions (personnel, organizational, financial, etc.), and achieving educational results.